Agrobiodiversity and resource supply to pollinators in agroforests in the Vale do Ribeira region, São Paulo - Gemim, Bruna Schmidt; Freitas, Miguel Luiz Menezes; Silva, Francisca Alcivania de Melo (Sustainability in Debate, 2025)
Agroforests are productive systems that can be managed with high species richness and based on practices that favour essential ecological interactions, imitating the functioning of forest ecosystems. To verify the agrobiodiversity managed in agroforests and the supply of floral resources to pollinators, this research was conducted with 20 family farmers who manage agroforests in nine municipalities in the Vale do Ribeira region, São Paulo. Through the guided tour, a great wealth of species and varieties was identified, around 350 in total. In the agroforests visited, the number of managed species varied from 25 to 93, with the best coverage of flowering species being from farmers who are already beekeepers. Among the managed species, there is a high number of native species from the Atlantic Forest Biome and food plants, which reinforces the potential of agroforests for the ethnoconservation of biodiversity and food and nutritional security. Furthermore, approximately 71% of the species are honey-producing, confirming the capacity of agroforests to provide food resources to pollinators. Considering that agroforestry stands out as an important strategy for promoting socio-environmental benefits and adapting to climate change, the results of this study reaffirm its potential in facing challenges and fulfilling commitments linked to sustainable development at a global level.